Determinan Investasi Asing Langsung di Indonesia: Analisis Empiris PDB, Stabilitas Politik, dan Rasio Pajak - Sabrina Anjani; Arintoko Arintoko; Herman Sambodo (Lingka Ekonomika, 2026)
Foreign Direct Investment (FDI) plays a strategic role in supporting Indonesia’s economic growth, although its realization tends to fluctuate due to various economic and non-economic factors. This study aims to examine the effects of Gross Domestic Product (GDP), political stability, and the tax ratio on FDI in Indonesia. A quantitative approach is employed using the Error Correction Model (ECM) method, with annual data from 1998 to 2023. The results indicate a long-run relationship among the variables, where the tax ratio and political stability have a positive and significant impact on FDI. In the short run, only political stability shows a positive effect on FDI. These findings highlight the importance of maintaining political stability and implementing supportive fiscal policies to sustainably attract foreign investment.